2018
DOI: 10.1038/s41388-018-0450-6
|View full text |Cite
|
Sign up to set email alerts
|

The miR-96 and RARγ signaling axis governs androgen signaling and prostate cancer progression

Abstract: Expression levels of retinoic acid receptor gamma (NR1B3/RARG, encodes RARγ) are commonly reduced in prostate cancer (PCa). Therefore, we sought to establish the cellular and gene regulatory consequences of reduced RARγ expression, and determine RARγ regulatory mechanisms. RARG shRNA approaches in non-malignant (RWPE-1 and HPr1-AR) and malignant (LNCaP) prostate models revealed that reducing RARγ levels, rather than adding exogenous retinoid ligand, had the greatest impact on prostate cell viability and gene e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 91 publications
(105 reference statements)
0
41
0
Order By: Relevance
“…The poorly invasive, androgen‐dependent LNCaP cell line expresses RARA and RARG mRNA, and RARα and RARγ, but not RARβ protein 34,35 . There are conflicting data regarding expression of RARB mRNA in LNCaP cells 34‐37 . DU145 and PC3 cells exhibit androgen‐independent growth and express RARA and RARG , but RARG mRNA, and also RARα and RARγ, but not RARβ 34,35 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The poorly invasive, androgen‐dependent LNCaP cell line expresses RARA and RARG mRNA, and RARα and RARγ, but not RARβ protein 34,35 . There are conflicting data regarding expression of RARB mRNA in LNCaP cells 34‐37 . DU145 and PC3 cells exhibit androgen‐independent growth and express RARA and RARG , but RARG mRNA, and also RARα and RARγ, but not RARβ 34,35 .…”
Section: Methodsmentioning
confidence: 99%
“…DU145 and PC3 cells exhibit androgen‐independent growth and express RARA and RARG , but RARG mRNA, and also RARα and RARγ, but not RARβ 34,35 . Human prostate epithelial non‐neoplastic RWPE‐1 cells 38 express RARα and RARγ, but not RARβ 37 . Cell cultures were maintained under serum‐free conditions using the Prostate Epithelial Cell Growth Medium (PrEGM) BulletKit (Cat.…”
Section: Methodsmentioning
confidence: 99%
“…These findings were further supported when considering target genes that were bound by PGC1α and differentially expressed in the TCGA cohort. These genes distinguished aggressive tumors and included RARγ/TACC1 24 , which we have previously established to antagonize AR signaling, as well as genes associated PPARγ signaling. Furthermore, motif analyses revealed that basic helix-loop-helix (b-HLH) motifs were enriched in the PGC1α ChromHMM sites, as were sites for LXR binding.…”
Section: Discussionmentioning
confidence: 99%
“…This re-wiring of AR signaling is mirrored by disrupted functions of other members of the nuclear hormone receptor super-family 11 , 24 , and probably occurs more widely to alter how transcription factors (TFs) function. Re-wiring of TFs changes the consequences of cell signaling and contributes to changes in lineage plasticity that are also associated with aggressive PCa 25 – 27 .…”
Section: Introductionmentioning
confidence: 99%
“…miR-96 governs androgen signalling and prostate cancer progression by regulating RARγ signal axis (Long et al. 2019 ). miR-205 can enhance radiation sensitivity of prostate cancer cells by impairing DNA damage repair through PKCε and ZEB1 inhibition (El Bezawy et al.…”
Section: Discussionmentioning
confidence: 99%